2004
DOI: 10.1183/09031936.04.00123903
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall kinematics and respiratory muscle action in ankylosing spondylitis patients

Abstract: No direct measurements of the pressures produced by the ribcage muscles, the diaphragm and the abdominal muscles during hyperventilation have been reported in patients with ankylosing spondylitis. Based on recent evidence indicating that abdominal muscles are important contributors to stimulation of ventilation, it was hypothesised that, in ankylosing spondylitis patients with limited ribcage expansion, a respiratory centre strategy to help the diaphragm function may involve coordinated action of this muscle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 30 publications
2
33
1
2
Order By: Relevance
“…In previous research into ventilation in ankylosing spondylitis, diaphragm contribution was estimated by the ratio between the chest wall and abdominal wall motion which was measured by magnetometer 3) , optoelectronic plethysmography 5) , and laser techniques 4) . These methods are indirect assessments of diaphragmatic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research into ventilation in ankylosing spondylitis, diaphragm contribution was estimated by the ratio between the chest wall and abdominal wall motion which was measured by magnetometer 3) , optoelectronic plethysmography 5) , and laser techniques 4) . These methods are indirect assessments of diaphragmatic function.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported recently that in ankylosing spondylitis, the upper chest wall motion is reduced while there is a normal range of lower chest wall and abdominal motion 4) . It has been indicated that ankylosing spondylitis patients are able to compensate for their limited upper chest wall motion by increasing diaphragm motion 4,5) . However, it is unclear whether in healthy subjects such a compensatory breathing pattern is induced by upper rib cage restriction.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of chest and abdominal wall mobility affects respiratory function and, in some cases, results in respiratory complications. A loss in mobility may be due to various factors such as aging, 1,2 scoliosis, 3,4 thoracoabdominal surgery, 5,6 ankylosing spondylitis, 7 and other chest wall diseases. 8 Therefore, chest and abdominal mobility assessments should be performed in a variety of clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Ribcage expansion is reduced but the abdominal expansion is preserved [248] as well as the diaphragmatic movement avoiding hypercapnic 'ventilator pump' failure [232] .…”
Section: Thoracic Cage Involvementmentioning
confidence: 99%
“…Men are far more frequently affected than women (16: 1) and more than 90% of Caucasians with the disease possess the HLA-B27 antigen [230] . Respiratory manifestations ( table 2 ) in ankylosing spondylitis are not uncommon and affect mainly the thoracic cage, the lungs in the form of an apical fibrobullous disease and obstructive sleep apnea syndrome (OSAS) [231][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246] (see online suppl. table 7).…”
Section: Ankylosing Spondylitismentioning
confidence: 99%